Aktivitas Antibakteri Ekstrak Metanol Daun Bidara (Ziziphus mauritiana Lam) Terhadap Bakteri Uji Penyebab Luka Infeksi Dengan Metode Difusi Agar - Irfanitha, irfanitha; Naid, Tadjuddin; Nuryanti, Siska (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Bidara leaves (Ziziphus mauritiana Lam) have the ability as an antibacterial, because they contain chemical compounds such as alkaloids, flavanoids, saponins, tannins and phenols. The content of phytochemical substances in bidara leaves accelerates the wound healing process on the outer skin. This study aims to determine the antibacterial activity of the methanol extract of bidara leaves (Ziziphus mauritiana Lam) against test bacteria that cause infectious wounds using the agar diffusion method. This test began with a screening test using 4 test bacteria and the results were inhibiting the growth of Staphylococcus aureus, Pseudomonas aeruginosa, Staphylococcus epidermidis and Propionibacterium acnes at concentrations of 0.1% and 0.5%. Then tested the antibacterial activity of the methanol extract of bidara leaves (Ziziphus mauritiana Lam) using the agar diffusion method and the result was that the ethanol extract of bidara leaves Ziziphus mauritiana Lam) has strong potential as an antibacterial against the test bacteria with the largest diameter of the inhibition zone at a concentration of 4% of 15 .00mm.